Coagulation Of Wood Pollutants From Model Wastewater By Aluminium Salts (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
One of the stages of raw material preparation for plywood producing is hydrothermal treatment of birch wood. Wastewater from plywood hydrothermal basin is characterized by the high degree of contamination. The basic contaminating component of this wastewater is lignin, hemicellulose and extractive substances (LES), which are the main reason of a high level of chemical oxygen demand (COD) and color of water. The main objective of the present study is to investigate the influence of aluminium sulfate, aluminium chloride and poly aluminium chloride dose on coagulation of LES from model wastewater. It was established that the influence of coagulant dose on LES removal can be described by 3 regions: first region - the process of coagulation does not take place; second region is characterized by the sharp increase of efficiency of LES removal and the third region corresponds to decrease of efficiency of LES removal at the increase of coagulant dose.